Chemical and Sensory Characteristics of Cookies from “Protani” Rice Flour that Affected by Source of Fat and Whey Protein - Sustriawan, Budi; Aini, Nur; Ramadani, Nurista Riski; Handayani, Isti; Safitri, Eka; Mustaufik, Mustaufik; Wicaksono, Rumpoko (Indonesian Journal of Food Technology, 2025)
The purpose of the study is to investigate how the kind of fat and the addition of whey protein affect the chemical and sensory characteristics of cookies made with modified Protani rice flour. The study used a Randomized Block Design (RBD). There were 2 factors studied, namely the type of fat and the addition of whey powder. The types of fat consisted of 3, namely margarine, a combination of margarine and virgin coconut oil (VCO) and VCO. The percentage of whey protein addition consisted of 3, namely 5, 10, 15%. The variables observed included water content, ash, fat, protein, reducing sugar, carbohydrates and sensory variables (color, aroma, texture, taste, and preference). Chemical and sensory variable data were analyzed using the Analysis of Variance (ANOVA) test and further using Duncan’s Multiple Range Test (DMRT) at the 95% level. The use of margarine can increase water, ash, protein and reducing sugar content, while virgin coconut oil (VCO) can increase fat and carbohydrate content. The higher the concentration of whey protein added, the higher the water, ash, fat, protein and reducing sugar content. The best cookies were obtained by using margarine and adding 15% whey protein, with a water content of 3.8%, ash 0.8%, fat 21.4%, protein 11.9% and reducing sugar 4.6%. The cookies have sensory properties of brownish yellow color (4.2), typical cookies aroma (4.4), slightly crumbly texture (3.7), slightly delicious taste (3.7) and liking (4.2). Cookies from fermented Protani rice flour have the potential to be developed into commercial products.